اللمفومات خارج العقدية والآفات المتعلقة بها - الشهابي, زهير; صالح, رنا (Latakia University Journal -Medical Sciences Series, 2019)
مقدمة:بالتعريف تعتبر اللمفوما خارج عقدية عندما توجد جل أو غالبية الآفة في موضع خارج العقد اللمفية تستلزم عادة توجيه المعالجة في المقام الأول إلى ذلك الموضع. تشمل المواضع الأكثر شيوعاً للمفوما خارج العقدية: السبيل الهضمي، الجلد، حلقة والداير، الغدد اللعابية، التيموس، ملحقات العين، الغدة الدرقية، الرئة والخصيتين. تهدف هذه الدراسة إلى إلقاء الضوء على الأنماط الرئيسية للمفومات الناشئة في مواضع خارج عقدية، ومناقشة اللمفومات خارج العقدية البدئية حسب تصنيف منظمة الصحة العالمية مع تظاهراتها السريرية ومظاهرها النسيجية المرضية وخصائصها المناعية. طرق الدراسة: تبين هذه الدراسة الخصائص المورفولوجية والمناعية لـ 58 حالة لمفوما خارج عقدية شخصت في قسم التشريح المرضي في مشفى الأسد الجامعي باللاذقية خلال الفترة بين عامي 1994- 2003. كانت العينات عبارة عن عينات جراحية، خزع تنظيرية، خزع جلدية. وإضافة إلى الطرق الروتينية في التشخيص والتلوين بـ H.E، استخدمت الملونات المناعية التالية لتأكيد التشخيص: LCA, CD20, CD3, CK, Bcl2, CD68, CD45R0, k & l light chains. النتائج: بين 58 حالة كان الموضع الأكثر شيوعاً للمفوما خارج العقدية هو جهاز الهضم 41 حالة، 27 منها في المعدة و14 حالة في الأمعاء وكانت أكثر أنماط اللمفوما تواتراً هي اللمفوما منخفضة الدرجة المرتبطة بالمخاطيات MALT Lymphoma 27 حالة بنسبة 66% يتلوها اللمفوما البائية كبيرة الخلايا المنتشرة 11 حالة بنسبة 27% ثم اللمفوما تائية الخلايا المترافقة مع الاعتلال المعوي حالتان بنسبة 5% والداء المناعي التكاثري للمعي الدقيق حالة واحدة بنسبة 2%. لمفومات الجلد جاءت في المرتبة الثانية من حيث الشيوع: 7 حالات توزعت بين فطار فطراني وأنماطه 3 حالات، حطاط لمفوماني حالة واحدة، لمفوما تائية عديدة الأشكال صغيرة/متوسطة حجم الخلية حالة واحدة، لمفوما بائية حالتان. فضلا عن لمفومات أخرى في مواضع متفرقة: لمفوما الغدة الدرقية حالة واحدة، لمفوما الثدي حالتان ، لمفوما منصفية بائية كبيرة الخلايا منتشرة حالتان، لمفوما نسج رخوة حالتان، لمفوما حلقة والدير حالة واحدة، لمفوما الخصية، حالة واحدة، لمفوما دماغ حالة واحدة. الخلاصة: قدمت هذه الدراسة فكرة عن تواتر حدوث اللمفوما خارج العقدية في اللاذقية خلال فترة 9 سنوات وعرضت المواضع والأنماط المختلفة لهذه اللمفومات لدى 58 مريض معتمدة على التصنيف الجديد لمنظمة الصحة العالمية والذي لا يقوم على المعايير الشكلية فقط وإنما على الخصائص المناعية والسريرية أيضاً مع إيلاء الأهمية لموضع نشوء كل نوع من اللمفوما مما يساعد على فهم أفضل للمرض وبالتالي تشخيصه ومعالجته بشكل صحيح . Background: By definition, a lymphoma is considered to be extranodal when it presents with the main bulk of disease at an extranodal site, usually necessitating the direction of treatment primarily to that site. The most common sites of involvement by extranodal lymphomas are the gastrointestinal tract, skin, Waldeyer's ring, salivary glands, thymus, ocular adnexa, thyroid gland, lung and testis. The aim of this study is to throw light on the major types of lymphomas on each extranodal site and discuss the primary extranodal lymphomas, as defined by the new WHO classification, giving all relevant information regarding clinical presentation, as well as histopathological, and immunophenotypic features. Materials and Methods: This study reveals the morphological and immunohistochemical features of 58 cases of extranodal lymphomas, diagnosed in the department of pathology at Al-Asad University hospital, Lattakia - Syria, during the period 1994-2003. Specimens were obtained from endoscopic and surgical biopsies.To confirm the diagnosis; we used immunohistochemical stains for LCA, CD 20, CD 3, CD43,CD10, BCL-2, Ki 67, Kappa and lambda light chains . Results: Among the 58 cases the most common site of extranodal lymphomas was the gastrointestinal tract, 41 cases, 27 involve the stomach, 14 involve the intestine. The most common type of these lymphomas was of MALT type (27 cases, 66%), followed by diffuse large B-cell lymphoma (11 cases, 27%), enteropathy associated T-cell lymphoma (2 cases, 5%) & immunoprolifeartive small intestinal disease (1 case, 2%). Skin was the second most frequently encountered 7 cases, Mycosis fungoides & variants (3 cases), Lymphomatoid papulosis (1 case), Pleomorphic CTCL, small/medium sized (1 case), Diffuse large B-cell Lymphoma (2 cases). Other miscellaneous extranodal lymphomas: thyroid lymphoma 1 case, breast lymphoma 2 cases, mediastinal diffuse large B-cell lymphoma 2 cases, lymphoma of Waldeyer's ring 1 case, lymphoma of the testis 1 case, lymphoma of soft tissue 2 cases, lymphoma of the brain 1 case. Conclusion: Our study indicates the incidence of extranodal lymphomas in Lattakia-Syria during 9 years and presents the different sites & patterns of these lymphomas in 58 Syrian patients giving the definition of each disease entity by the new classifications, based not only on morphological,but on immunohistochemical, and clinical data as well, and giving importance to the site of origin of each tumour will help us better understand, and subsequently diagnose and treat this group of tumours.